Quantification of Serum Free RNA as a Predictive Biomarker for the Response to Chemotherapy in Patients with Lung Cancer: A Pilot Study - Um, Soo-Jung; Lee, Su-Mi; Lee, Soo-Keol; Son, Choonhee; Ko, Mee Kyung; Roh, Mee Sook; Lee, Ki Nam; Choi, Pil Jo (Tuberculosis and respiratory diseases, 2011)
Background: It is well-known that cell-free nucleic acids rise in patients with many types of malignancies. Several recent experimental studies using cancer cell lines have shown that changes in cell-free RNA are predictive of the response to chemotherapy. The objective of this study was to determine whether quantification of free RNA can be used as a biomarker for clinical responses to chemotherapy in patients with lung cancer. Methods: Thirty-two patients with lung cancer (non-small cell lung cancer, n=24; small cell lung cancer, n=8) were divided into 2 groups according to their responses to chemotherapy (response group, n=19; non-response group, n=13). Blood samples were collected before and after two cycles of chemotherapy. Real-time quantitative RT-PCR was used for transcript quantification of the glyceraldehyde-3-phosphate dehydrogenase gene. Results: The pre chemotherapy values (Response group 41.36±1.72 vs. Non-response group 41.33±1.54, p=0.78) and post chemotherapy values (Response group 39.92±1.81 vs. Non-response group 40.41±1.47, p=0.40) for cell free RNA concentrations, expressed as Ct GAPDH (threshold cycle glyceraldehyde-3-phosphate dehydrogenase gene) levels, was not different between the two groups. There was no significant relationship between changes in the cell free RNA level clinical responses after chemotherapy (p=0.43). Conclusion: We did not find a correlation between quantification of serum cell free RNA levels and clinical responses to chemotherapy in patients with lung cancer. Further investigations are needed to determine whether the cell free RNA level is a useful predictor of responses to chemotherapy in patients with lung cancer. KCI Citation Count: 0